Diagnosis of multiple sclerosis: revisions of the McDonald criteria 2017 - continuity and change - Hartung, Hans-Peter; Graf, Jonas; Aktas, Orhan; Mares, Jan; Barnett, Michael H (Current opinion in neurology, 2019)
PURPOSE OF REVIEW: The purpose of this review is to describe the new 2017 revisions of the McDonald diagnostic criteria for multiple sclerosis and review first experiences in their application to different patient populations. RECENT FINDINGS: The 2017 revisions agreed on by an international expert panel, as the precursors, define criteria needed to fulfill dissemination in time and space in the clinically isolated syndrome after exclusion of alternative diagnoses. One major change is the inclusion of cerebrospinal fluid (CSF) oligoclonal bands as evidence of dissemination in time in a patient with dissemination in space gathered by clinical or magnetic resonance examination. The distinction between asymptomatic and symptomatic lesions in counting for evidence of dissemination in space or time in supra, infratentorial, and spinal cord syndrome has been abandoned. Finally, cortical lesions can be used to demonstrate dissemination in space. Major differential diagnoses, in particular, the still-evolving concept of neuromyelitis optica spectrum disorders and the myelin oligodendrocyte glycoprotein-IgG-related demyelinating central nervous system disorders. SUMMARY: The new 2017 revisions will simplify the application of the MRI criteria for dissemination in space and include CSF findings as evidence for dissemination in time in clinically isolated syndrome.
Keywords: Magnetic Resonance Imaging; glykoprotein v myelinu oligodendrocytů; Myelin-Oligodendrocyte Glycoprotein; magnetická rezonanční tomografie; Humans; Neuromyelitis Optica; roztroušená skleróza; lidé; neuromyelitis optica; Multiple Sclerosis